The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1126/science.6177040
|View full text |Cite|
|
Sign up to set email alerts
|

Transformation Induced by Abelson Murine Leukemia Virus Involves Production of a Polypeptide Growth Factor

Abstract: Rat embryo fibroblasts transformed by Abelson murine leukemia virus (MuLV) produce and release a transforming growth factor (TGF). Production of this factor is correlated with a tyrosine-specific protein kinase that is functionally active and is associated with the major Abelson MuLV gene product, P120. Transformation-defective mutants of Abelson MuLV do not transform cells, do not have their virus coded transforming gene product phosphorylated in tyrosine, and do not induce TGF production. Abelson MuLV-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
43
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 23 publications
8
43
0
Order By: Relevance
“…Before leaving autocrine mechanisms for growth factor independence, we should mention that previous work demonstrated that fibroblasts transformed by A-MuLV secrete transforming growth factor alpha, which binds to and acts via the epidermal growth factor receptor (36). We consider this potential autocrine mechanism unlikely to be the basis of PDGF independence in our assay, since epidermal growth factor cannot substitute for PDGF in our defined media to support fibroblast growth (43).…”
mentioning
confidence: 92%
“…Before leaving autocrine mechanisms for growth factor independence, we should mention that previous work demonstrated that fibroblasts transformed by A-MuLV secrete transforming growth factor alpha, which binds to and acts via the epidermal growth factor receptor (36). We consider this potential autocrine mechanism unlikely to be the basis of PDGF independence in our assay, since epidermal growth factor cannot substitute for PDGF in our defined media to support fibroblast growth (43).…”
mentioning
confidence: 92%
“…Since feeder layer dependence in vitro seems to be related to the production of soluble factors produced by the adherent cell layer (8), it is conceivable that the 6C3 proteins on independently growing B lineage cells may represent novel B-cell growth factors or receptors for growth factors or other molecules. In this regard it is interesting to note that A-MuLV-transformed fibroblasts produce a tumor growth factor that competes with epidermal growth factor for binding (28). In any event, further characterization of the structure and function of the 6C3 proteins should provide new insights into the process of B-lymphocyte transformation.…”
mentioning
confidence: 99%
“…It has been shown that certain virally transformed cells, but not the nontransformed control cells, secrete type a TGFs (8,9,20,30 TGF (8,9,20,30) and PDGF (6) and their corresponding receptors after transformation.…”
mentioning
confidence: 99%
“…Chem., in press), have a molecular weight of 25,000 and are composed of two apparently identical polypeptide chains cross-linked by disulfide bonds (5,11,23). Type at (13,(17)(18)(19)30) and p (5,7,11,21,23,24) with 10% calf serum, penicillin (50 U/ml), and streptomycin (50 ,ug/ml) and were incubated in humidified 5% C02-95% air at 37°C. After 2 days, when cells were nearly confluent, monolayers were washed gently three times every 2 h with (serum-free medium and then further incubated with serumfree medium.…”
mentioning
confidence: 99%